The manufacture of glacial acetic acid by submerged fermentation: A project study - Gaspar, Fernando (Animo Repository, 1973)
Name of the Firm: Acid Makers, Incorporated. Location: Pre-operating Office - 44 Hercules Street, Makati, Rizal. Proposed Plant - Barrio Malanday, Marikina, Rizal. Brief Description of the Project. Acid Makers, Incorporated, a proposed corporation to be registered with the Securities and Exchange Commission, proposes to establish an acetic acid manufacturing plant with a rated annual capacity of 2240 tons at 100% capacity. The plant will manufacture glacial acetic acid for use in the textile industry, the food industry, the paint industry and the pharmaceutical industry. The raw materials to be used are molasses and ethyl alcohol, both to be locally supplied. The project will supply the domestic demands. The plant has been designed to expand to meet possible export market requirements. The project is estimated to entail a total investment of P3,000,000. It cannot be registered with the BOI because it is neither a pioneer nor a preferred project. Equipment will be locally fabricated. Knowhow will come from Filipino engineers and chemists. Plant construction and equipment installation will be undertaken by Filipino contractors. Major Assumptions. Market Assumptions. 1. The local demand for glacial acetic acid (commercial grade) has been observed to be 2,275,000 kilos in 1971 and has been computed to rise at a conservative estimate of 10.7% annually. 2. The delivered selling price is P43/20 kilos in 1974-75 and P45/20-kilos in 1976-83 for market strategy A. 3. The delivered selling price is P45/20 kilos in 1974-75 and P47/20-kilos in 1976-83 for market strategy B. 4. Annual finished goods inventory is maintained at 10 days of operations for 1974 15 days of operations for the succeeding years. 5. Accounts receivable are 60 days of sales. 6. Raw materials inventory is 30 days of raw materials costs. Technical Assumptions. 1. Fermenter efficiency is 98% conversion to acetic acid (10% HAc). 2. Extraction efficiency is 98-99%. 3. Mash contains 0.1-0.2% acetic acid. 4. Over-all process efficiency exceeds 90%. 5. Solvent (ethyl acetate) absorbs 3.3 kgs H2O per 100 kgs. solvent. 6. Water to alcohol ratio is 10:1. 7. Acetic acid coming out of the concentration column is 99.9% pure. Financial Assumptions. 1. The project will be financed through stockholders' contribution and a 50-50 equity long-term loan. 2. P1,500,000 will be obtained from equity participation P1,500,000 will be obtained from a bank loan at 12% interest per annum for a 10 year period to amortize. 3. There has been no assumption concerning tax exemptions.